EUROPEAN UNION AND THE COMPETITION FOR A NEW WORLD ORDER - Brigadier-general (ret.) Professor Mircea UDRESCU, Ph.D (Annals: Series on Military Sciences, 2023)
For the European states, the declared goal of the European Union is to achieve a high level of prosperity. The EU has continuously expanded, and the US has encouraged the expansion in order to have a collective entity to follow its geopolitical and geostrategic initiatives. But the Union believes that the time has come for it to become more and more independent and sovereign in the new international environment, this idea being especially embraced by countries such as Germany, France and Italy, but not only. The commitments of the EU alongside the US in the war in Ukraine led to the destruction of the ideals of prosperity dreamed of by the nations of the European Union.